Implementasi Strategi Manajemen Sumber Daya Manusia dalam Meningkatkan Kinerja Karyawan Industri Putra Fiber di Kecamatan Grogol Kabupaten Sukoharjo - Bagas Nur Pangestu; Abu Bakar Akbar (PENG: Jurnal Ekonomi dan Manajemen, 2026)
This study examines the implementation of human resource management (HRM) strategies at Putra Fiber, a medium-sized micro-industry in Sukoharjo, to understand its role in improving employee performance. The research approach used is descriptive qualitative with deductive analysis, where data is collected through observation, interviews, and documentation studies. The results of the analysis show that although essential HRM functions (procurement, training, compensation) are carried out informally, these practices are quite effective. The obstacles identified include: (1) the absence of a structured recruitment and training system; (2) the lack of career paths; (3) the absence of documented work SOPs. The main strengths lie in the open communication culture and familial relationships. The recommendation is that HRM systems need to be formalised, particularly through the development of SOPs and training programmes, in order to improve the quality and sustainability of the organisation's performance.